(untitled) - Whaley, Robert E. (Hoboken, N.J., 2006)
Robert Whaley has more than twenty-five years of experience in the world of finance, and with this book he shares his hard-won knowledge in the field of derivatives with you. Divided into ten information-packed parts, Derivatives shows you how this financial tool can be used in practice to create risk management, valuation, and investment solutions that are appropriate for a variety of market situations.
Keywords: Derivative securities,Derivative securities,Chứng khoán phái sinh,Chứng khoán phái sinh; Marketing,Valuation,Tiếp thị,Đánh giá